A mixed-methods evaluation of a longitudinal primary–secondary school transitions support intervention - Bagnall, Charlotte Louise; Stevenson, Elizabeth; Cookson, Darel; Jones, Frederick; Garnett, Nicholas James (Frontiers in Psychology, 2024)
Introduction Primary–secondary school transitions are critical transitions for children that can be emotionally demanding longitudinal experiences, which can positively and negatively impact future emotional wellbeing and mental health. However, interventions that have been developed to reduce the negative outcomes children commonly experience are limited in number, sustainability, and reach and rely on a cross-sectional approach, as opposed to longitudinal evaluations. The current study evaluates Transitions 5–7, a universal, class-based 9-week intervention to develop children’s awareness and ability to cope with the multiple changes experienced over primary–secondary school transitions. Methods The evaluation utilized a mixed-methods approach, combining both quantitative outcome and qualitative process intervention evaluation. For the outcome evaluation, a quasi-experimental research design was used, and children of the intervention and comparison groups completed a questionnaire in Year 5 (n = 185), Year 6 (n = 217), and Year 7 (n = 162), which assessed their self-reported perception of Transitions Worries, Transitions Excitement, Emotional Wellbeing, Parental Support, and Coping Efficacy. To understand the implementation of Transitions 5–7, three focus groups were conducted with Year 6 children, 3 interviews with teachers, and 1 interview with the Transitions Manager of the local government education authority during the project, who developed Transitions 5–7. Results The outcome evaluation found that children participating in the intervention showed a decrease in Transitions Worries and an increase in Transitions Excitement and Coping Efficacy compared with the comparison group, resulting in a lowered impact on Emotional Wellbeing over time. The need for a more systemic approach to primary–secondary school support provision, which is gradual, has a distinct delivery and follows a skills-based curriculum, was discussed in the process evaluation. Meta-inferences drawn demonstrate the importance of gradual emotional centered transitions provision embedded within Years 5, 6, and 7. Discussion The present study makes a unique empirical contribution in demonstrating the need and viability to take a preventative as opposed to a curative approach to primary–secondary school transitions support provision and begin early in Year 5. Conceptual and methodological implications for future research and implications for educational policy and practice are discussed.